2017
DOI: 10.1007/s00737-017-0767-0
|View full text |Cite
|
Sign up to set email alerts
|

Improving help-seeking for postnatal depression and anxiety: a cluster randomised controlled trial of motivational interviewing

Abstract: Low uptake of treatment by women with symptoms of postnatal depression and anxiety is consistently reported. This study examined whether a brief motivational interviewing (MI) intervention delivered by Maternal and Child Health Nurses (MCHNs) during routine emotional health assessments improves help-seeking following childbirth. In this parallel two-group cluster randomised controlled trial, MCHNs delivered a MI intervention ('PRIMER', n = 20) or Routine Care (n = 20) at women's (n = 541) postnatal consultatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
1
20
0
2
Order By: Relevance
“…There is also a possibility that symptoms were played down/ underreported due to the stigma associated with mental health disorders in many African cultures [45, 46]. Women may worry that their child caring capacity may be called into question and they may also be reluctant to take up treatment interventions involving prescription drugs while breastfeeding [10, 17, 47]. On average 50% of depressed women often go undiagnosed, with only 20% of those diagnosed seek treatment [11–13, 47].…”
Section: Discussionmentioning
confidence: 99%
“…There is also a possibility that symptoms were played down/ underreported due to the stigma associated with mental health disorders in many African cultures [45, 46]. Women may worry that their child caring capacity may be called into question and they may also be reluctant to take up treatment interventions involving prescription drugs while breastfeeding [10, 17, 47]. On average 50% of depressed women often go undiagnosed, with only 20% of those diagnosed seek treatment [11–13, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to currently available screening methods, after a brief assessment to detect mothers at risk for postpartum depression, clinicians would have more time available to explore symptoms, provide psychoeducation, and boost patients' treatment motivation, actions that may help to reduce the treatment gap for postpartum depression. For instance, recently Holt et al (2017) have demonstrated that a brief motivational interviewing intervention during well‐child check‐ups can increase treatment uptake for postnatal depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, busy primary care clinicians (i.e., a nurse or a physician) who have half an hour to conduct a thorough, comprehensive evaluation of the child's growth and provide guidance to parents and/or caregivers, are also in charge of the administration of the screening for postpartum depression (Chilean Ministry of Health, 2014). In this context, although administering the EPDS is feasible in 5 min, this instrument might be long enough to represent a missed chance for providing tailored information about test results, briefly educate mothers about postpartum depression, and motivating access to treatment for depressed mothers (Holt, Milgrom, & Gemmill, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Aufgrund der zum Teil lang andauernden psychischen Störungen sollten Mütter frühzeitig über die Möglichkeit informiert werden, eine Familienhebamme zu beantragen, um eine zusätzliche Betreuung im ersten Lebensjahr des Kindes zu gewährleisten. [45].…”
Section: Merkeunclassified